Research progress in the treatment of lipid metabolism disorder in patients with diabetic kidney disease by the integrated traditional Chinese and Western medicine - Lingli Sheng; Lingli Sheng; Ziyi Cao; Lin Wang; Youhua Xu; Dingkun Gui; Dingkun Gui (Frontiers in Endocrinology, 2025)
Diabetic kidney disease (DKD) is one of the most common and severe chronic microvascular complications of diabetes mellitus (DM). The pathogenesis of DKD is complex, and lipid metabolism disorders play an important role in the pathogenesis of DKD. DKD belongs to the category of “kidney deficiency”, “edema”, “guan ge” and other pathological factors secondary to “thirst quenching disease” in traditional Chinese medicine. The pathological factors mainly focus on blood stasis and toxicity, which is consistent with modern medical theory. At present, the efficacy and safety of integrated traditional Chinese and Western medicine in treating lipid metabolism disorders in patients with DKD have been extensively studied and confirmed. In this review, the application and possible mechanism of traditional Chinese patent medicines (Bailing Capsule, Shenyan Kangfu Tablets, Jinshuibao Capsule, Huangkui Capsule, Yi-Shen-Hua-Shi granule, Shenmai injection), Chinese medicine compound (Tangshen Formula, Danggui Buxue Decoction, Tangshenkang), single Chinese medicine (Astragalus membranaceus, Panax notoginseng, Salvia miltiorrhiza) combined with Western medicine in the treatment of DKD with lipid metabolism disorder were discussed, in order to provide ideas for clinical diagnosis and treatment of patients with DKD with lipid metabolism disorder.